PIJAT BAYI MEMPENGARUHI KADAR KORTISOL DAN KUANTITAS TIDUR BAYI YANG MENGALAMI HOSPITALISASI DENGAN PENDEKATAN TEORI COMFORT KOLCABA - Ernawati, Dwi (Universitas Nahdlatul Ulama Surabaya, 2014)
The baby was ill and hospitalized has plenty of noisy environment stressor, painful and uncomfortable. The condition can cause a crisis caused by changes in the environment.. The purpose of this research was to prove the influence of baby massage in reducing levels of cortisol and increases the quantity of baby having hospitalisasi in the 2nd floor Marwah RSU Haji Surabaya. This type of research is experimental pre-test and post test control group design. Sampelnya are some babies with diarrhea hospitalized at Room 2nd floor Marwah RSU Haji Surabaya in may 2013 with a total of 20 respondents (10 respondents as a group treatment and 10 respondents as the control group). Baby massage is performed by therapists in the treatment group. Data collection using the observation sheet. The t-test analysis bivariat use to prove there are differences in the levels of cortisol and quantity of baby massage is performed before and after the babies with 5% significance (? = 0.05). The results showed that cortisol saliva on the Group's treatment has decreased significantly. T test shows p = 0.01, meaning there's a baby massage influences on salivary cortisol levels decrease in the Group's treatment and test t to quantity of sleep baby shows p = 0,004, which means there is influence on increasing the quantity of baby massage beds from babies who are having hospitalisasi in the 2nd floor Marwah RSU Haji Surabaya. The conclusions of this research shows that massage the baby effect in lowering the levels of cortisol and increases the quantity of baby having hospitalisasi in the 2nd floor Marwah RSU Haji Surabaya. More research needs to be developed to make baby massage model appropriate and effective in reducing stress of infants who experience hospitalisasi.